Carbon Monoxide Poisoning due to Gas Water Heater - Bista, Bidesh; Manandhar, Dhiraj; Mishra, Rupesh; Shrestha, Pradeep; Dhungel, Alok (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Carbon Monoxide (CO) poisoning is a leading cause of injury and death due to poisoning in many parts of the world. Among numerous sources of CO, the gas water heater can be a potential under looked source causing an accidental Carbon monoxide poisoning. In the perspective of Kathmandu valley, where there are houses with small bathrooms, inadequate ventilation and absent CO detectors, gas water heaters can be extremely dangerous even if it liberates small amount of CO gas. Herein, we present a case of CO poisoning to increase awareness about the gas water heater use and the possible risk of CO poisoning in our community. Presentation of Case: A 34 years old healthy female from Patan, presented with the history of loss of consciousness for 15 minute while taking bath on a gas water heater. There was no spontaneous respiration, no cardiac activity and her body temperature was below normal. Discussion: CO is toxic to all aerobic forms to life. CO binds to hemoglobin 230 times faster than oxygen causing cellular hypoxic damage and death. CO poisoning is not uncommon in our society and many such cases are misdiagnosed for some other illness. Conclusion: Use of the gas water heaters and likelihood of CO poisoning should be notified as a public concern. People need to be aware of these hazards to prevent fatal events and likely death due to exploitation of gas water heaters. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 56-59